On generalized derivations involving prime ideals with involution - Rehman, Nadeem ur; Alnoghashi, Hafedh M.; Hongan, Motoshi; Rehman, Nadeem ur; Alnoghashi, Hafedh M.; Hongan, Motoshi (Institute of Mathematics, NAS of Ukraine, 2023)
UDC 512.5 We study the structure of the quotient ${A}/P$, where ${A}$ is any ring with involution $*$ and ${P}$ is a prime ideal of ${A}$. With an aim to construct a ring with involution of this kind, we study the behavior of generalized derivations satisfying the algebraic identities involving prime ideals. As a consequence, currently existing results in this field are enhanced.